2013
DOI: 10.1111/pce.12218
|View full text |Cite
|
Sign up to set email alerts
|

The purine metabolite allantoin enhances abiotic stress tolerance through synergistic activation of abscisic acid metabolism

Abstract: Purine catabolism is regarded as a housekeeping function that remobilizes nitrogen for plant growth and development. However, emerging evidence suggests that certain purine metabolites might contribute to stress protection of plants. Here, we show that in Arabidopsis, the intermediary metabolite allantoin plays a role in abiotic stress tolerance via activation of abscisic acid (ABA) metabolism. The aln loss-offunction of ALN, encoding allantoinase, results in increased allantoin accumulation, genome-wide up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 49 publications
12
150
1
1
Order By: Relevance
“…Recently, the constitutive accumulation of allantoin was shown to improve overall plant performance under stress by activating abscisic acid signaling pathways (Wang et al, 2012), and exogenous application mitigated oxidative damage symptoms (Watanabe et al, 2014). Here, we show that pretreating barley roots with physiologically relevant concentrations of exogenously applied allantoin desensitized the root apical tissues and increased their ability to retain K + upon both salinity and ROS exposure (Fig.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Recently, the constitutive accumulation of allantoin was shown to improve overall plant performance under stress by activating abscisic acid signaling pathways (Wang et al, 2012), and exogenous application mitigated oxidative damage symptoms (Watanabe et al, 2014). Here, we show that pretreating barley roots with physiologically relevant concentrations of exogenously applied allantoin desensitized the root apical tissues and increased their ability to retain K + upon both salinity and ROS exposure (Fig.…”
supporting
confidence: 51%
“…Given the recent reports for the mitigating role of allantoin in oxidative stress damage in plants (Watanabe et al, 2014), we tested the effects of exogenously supplied allantoin on root ion flux responses to ROS. Root pretreatment with a physiologically relevant (1 mM) concentration of allantoin reduced the sensitivity of the root apex to both salinity and ROS stresses (Fig.…”
Section: Exogenous Application Of Allantoin Reduced the Extent Of Rosmentioning
confidence: 99%
“…Although not conspicuous in the GO analysis (Table 1 of Watanabe et al, 2014b), the aln mutants also showed increased expression of JA response signatures including genes involved in JA metabolism and signaling, such as 13-LIPOXYGENASE (LOX) and JASMONATE ZIM-DOMAIN (JAZ) PROTEINS (Supplementary Table S2 of Watanabe et al, 2014b). For this reason, and to improve the interpretation of the transcriptome profiles, the first step in this study was to renormalize these microarray data according to a three-parameter lognormal distribution model (Konishi, 2004).…”
Section: The Aln Mutants Show Increased Expression Of Abaand Ja-respomentioning
confidence: 99%
“…Functional enrichment analyses of the Biological Process Gene Ontology (GO) terms were carried out using the BioMaps tool of VirtualPlant version 1.3 (Katari et al, 2010;http For quantitative transcript analysis, samples of aerial parts were collected from 2-week-old seedlings that were grown aseptically on solid 1/2MS medium with or without added allantoin (Wako Pure Chemical Industries, Ltd, Osaka, Japan) or allantoic acid (Carbosynth Limited, Berkshire, UK). RNA extraction and real-time reverse transcription quantitative PCR (RT-qPCR) were performed as described previously (Watanabe et al, 2014b). Relative gene expression levels were calculated by the 2 −∆∆Ct method (Livak and Schmittgen, 2001) after normalization to ACTIN2 expression levels.…”
Section: Gene Expression Analysesmentioning
confidence: 99%
See 1 more Smart Citation